Letter from J. Graves to James Curtis Booth, March 30, 1854 - Graves, Jackson (1854)
A request to take courses with James Curtis Booth (1810-1888).
Keywords: Booth, James Curtis, 1810-1888; Chemistry teachers; Lectures and lecturing